Taxation and the Peer-to-Peer Economy - Aslam, Aqib (IMF Working Papers; Working Paper ;, 2017)
The growth of the peer-to-peer (P2P) economy over the last decade has captivated both stock markets and policymakers alike. While the means for transacting might be different to existing firm structures-with the emergence of digital platforms that connect individual buyers and sellers directly-the tax behavior of individuals operating in this new economy are very familiar. What is clear is that while the P2P economy has potentially exacerbated existing policy, administrative, and revenue-mobilization challenges associated with small business taxation-such as the choice of the tax base and how to set tax thresholds-, the technology behind P2P platforms presents a valuable opportunity to eventually solve them.